Efeito neuroprotetor da Spirulina platensis em camundongos submetidos ao modelo de Doença de Alzheimer esporádica induzida por estreptozotocina - Tavares, Juliete (2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disease that causes gradual memory loss and cognitive impairment. Intracerebroventricular injections of streptozotocin (ICV-STZ) have been used as an experimental model of sporadic Alzheimer's disease (SAD) because they produce deficits in brain insulin signaling, oxidative stress, neuroinflammation, and neurodegeneration, resulting in cognitive decline and memory impairment. Spirulina platensis (SPI) is a nutraceutical with anti-inflammatory, antioxidant, and neuroprotective properties. The objective of this work was to study the effects of SPI on cognitive deficits and neuronal damage in mice submitted to the experimental model of SAD induced by ICV-STZ. Male Swiss mice (weighing 25–35 g) received ICV-STZ (3 mg/kg) bilaterally on days 1 and 3 of the experiment. SPI (50 and 100 mg/Kg, p.o.) or vehicle (saline) was administered 2 hours after the second surgery, once a day for 16 days. The results showed that there was no change in blood glucose. SPI treatment prevented working, episodic, spatial, and aversive memory deficits. Locomotor activity and parameters related to anxiety in the EPM were not altered. ICV-STZ caused an increase in MDA, nitrite, and superoxide anion, while decreasing GSH. SPI treatment protected against this increase and increased GSH in the prefrontal cortex and hippocampus. It inhibited AChE activity in the prefrontal cortex. ICV-STZ caused astrogliosis and microgliosis, decreased the number of BDNF-immunoreactive neurons, and caused neuronal death in the prefrontal cortex and hippocampus. Treatment with SPI prevented astrogliosis, microgliosis, and neuronal death, but it was not effective in preventing BDNF depletion. Molecular docking analyses showed that phycocyanobilin was tightly bound to AChE and IRS-1 targets. These findings highlight the therapeutic potential of SPI for the treatment of SAD, indicating that its neuroprotective action is linked to antioxidant, anti-inflammatory, and AChE inhibitory activities.